ANALISIS DAYA SAING KOSMETIK KOREA SELATAN DENGAN KOSMETIKA INDONESIA DI PASAR INDONESIA - Apriyani, Ni Putu Winda; Setyari, Ni Putu Wiwin (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 10 (2021): VOL 10 NO 10, OKTOBER 2021 [3966 - 4405], 2021)
Cosmetics are daily necessities that are often used to treat skin or face and also to beautify themselves. The cosmetics industry that is in demand right now is from the South Korean country, South Korea. The influence of culture and quality of products made from natural ingredients with the sophistication of the technology makes Indonesian people interested in South Korean cosmetic products. The objectives of this study are (1) to analyze the competitiveness of South Korean cosmetics and Indonesian cosmetics in the Indonesian market (2) analyze and test the relationship between relative price, relative quality of South Korean cosmetics and Indonesian cosmetics to the competitiveness of South Korean cosmetics in the Indonesian market. The data used in this study are secondary data, analyzed using Market Share Analysis, Revealed Comparative Advantage (RCA), and Correlation Analysis. The results show that (1) imports of South Korean cosmetics in the Indonesian market have increased every year (2) Indonesian cosmetics are able to compete with South Korean cosmetics in their own markets (3) Relative prices, relative product quality shows a correlation with the competitiveness of South Korean cosmetics in the Indonesian Market. Means that price and product quality are related and affect competitiveness. This means that Indonesian cosmetics have not been able to compete with South Korean cosmetics in the Indonesian market in terms of price and product quality. Keywords : Cosmetic Competitiveness, RCA, Market Share, Price, Product Quality